XBB.1.16‐RBD‐based trimeric protein vaccine can effectively inhibit XBB.1.16‐included XBB subvariant infection - Dandan Peng; Cai He; Zimin Chen; Hong Lei; Xiya Huang; Chunjun Ye; Binhan Wang; Ying Hao; Xinyi Du; Shuaiyao Lu; Hongbo Hu; Wei Cheng; et al. (MedComm, 2024)
Abstract The newly identified XBB.1.16‐containing sublineages, including XBB.1.5, have become the prevailing severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) variant in circulation. Unlike previous Omicron XBB variants (e.g., XBB.1.5 and XBB.1.9) harboring the F486P substitution, XBB.1.16 also carries a T478R substitution in the receptor‐binding domain (RBD). Numerous researchers have delved into the high transmissibility and immune evasion of XBB.1.16 subvariant. Therefore, developing a new vaccine targeting XBB.1.16, including variants of concern (VOCs), is paramount. In our study, we engineered a recombinant protein by directly linking the S‐RBD sequence of the XBB.1.16 strain of SARS‐CoV‐2 to the sequences of two heptad repeat sequences (HR1 and HR2) from the SARS‐CoV‐2 S2 subunit. Named the recombinant RBDXBB.1.16‐HR/trimeric protein, this fusion protein autonomously assembles into a trimer. Combined with an MF59‐like adjuvant, the RBDXBB.1.16‐HR vaccine induces a robust humoral immune response characterized by high titers of neutralizing antibodies against variant pseudovirus and authentic VOCs and cellular immune responses. Additionally, a fourth heterologous RBDXBB.1.16‐HR vaccine enhances both humoral and cellular immune response elicited by three‐dose mRNA vaccines. These findings demonstrate that the recombinant RBDXBB.1.16‐HR protein, featuring the new T478R mutation, effectively induces solid neutralizing antibodies to combat newly emerged XBB variants.